Aliran Batiniah; Dulu dan Sekarang - Kholili Hasib (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2016)
Batiniah is a particular faith that believes the most important quality in everything spirituality (batin), not physically (zahir). Batin is the essence and nature (hakikat), whereas zahir is unreal sightings. This faith goes into several sects that form their own beliefs. Its influence gets into the sects of Shi’ism philosophy, Ibahiyah, and others. In it development of faith gives influence to the teaching of syncretism, pluralism, and abortion of beliefs to sharia obligations. Finally, some famous scholars paid attention to their teachings. For example Imam al-Ghazali who wrote a special note of criticism against this sect in his book Faḍāiḥ al-Bāṭiniyyah. He explained that the characteristics of Batiniah is to deny the literal meaning of the Qur’an and Hadith. In addition, Imam Abu al-Fadl Qadi Iyad, in al-Syifā bi Ta’r īfi Ḥuqūq al-Muṣṭafa, explained that Batiniah, are those who believes that sharia and a large part of the message brought by the Prophets did not correspond to their inner meaning. This doctrine actually is a mixture of the teachings of Neo-Platonism, Aristotelian philosophy, Zoroastrianism, Judaism, and Islam. So that Batiniah can be said as the faith of syncretism comes into the sects of Islam. Although it has grown and divided since it’s beginning, the basic beliefs are still consistent, that the batin is real and zahir is not real. Thus it tends to trust dualism, the essentials of everything is batin, not the zahir.